Model Sekolah Adiwiyata Melalui Program Asistensi Mengajar Berbasis Pembelajaran Experiential - Wahyuni, Lilik; Riyanto, Sugeng (Jurnal Paedagogy, 2022)
The study aims to get descriptions of (1) collaboration between teachers and students; (2) the development of Adiwiyata school model; and (3) optimizing Adiwiyata schools through a teaching assistance program based on experiential learning. This study used a qualitative descriptive method with a survey and development research design. The data sources of this research were the residents of SMP 12 Malang and students of the teaching assistance program at the Faculty of Agriculture, Universitas Brawijaya. The key instrument of this research was the researcher, assisted by using a questionnaire instrument and observation and interview guidelines. Data analysis was carried out through the stages of (1) data review, (2) data category and classification, (3) data reduction and codification, and (4) drawing conclusions. The research showed (1) students and teacher collaboration in an experiential learning-based teaching assistance program was the students manage the learning in the Concrete Experience and Active Experimentation stages while the teacher manages the learning in the Reflective Observation and Abstract Conceptualization stages; (2) the development of the Adiwiyata school model through the experiential learning-based teaching assistance program was carried out by reviewing the school's vision, mission, and goals, developing a learning plan using the experiential learning method, and developing an environment-based learning arena; and (3) optimization of Adiwiyata schools through experiential learning-based teaching assistance programs was carried out through habituation with a participatory approach.